PENGARUH KREATIVITAS, INOVASI DAN REVIEW PRODUK DI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN PADA MEPHOTO_PROJECT - Hansel Agustinus; Saortua Marbun (Universitas Triatma Mulya, 2020)
This research is triggered by the phenomenom of purchasing decisions on the online store Mephoto_Project. This research is used to analyze and prove the effect of reativity, innovation, and review of purchasing decisions. Quantitative methods use for this research. The sample technique used is incidental sampling technique. The numbrt of respondents are 105 consumers. Multiple linear regression analysis using SPSS software version 24. Regression equation obtained: Y = 5,063 + 0,251X1 + 0,257X2 + 0,212X3. This research has results indicate that: First, creativity has a positive impact on purchasing decisions on Mephoto_Project. Second, innovation has a positive impact on purchasing decision on Mephoto_Project. Third, the review has a positive impact on purchasing decision on Mephoto_Project. Fourth, the amount of influence contributed by creativity, innovation, and review of purchasing decisions on Mephoto_Project is 18.9%